Low-energy phenomenology of scalar leptoquarks at one-loop accuracy - Valerio Gherardi; David Marzocca; Elena Venturini (Journal of High Energy Physics, 2021)
Abstract We perform a complete study of the low-energy phenomenology of S 1 and S 3 leptoquarks, aimed at addressing the observed deviations in B-meson decays and the muon magnetic dipole moment. Leptoquark contributions to observables are computed at one-loop accuracy in an effective field theory approach, using the recently published complete one-loop matching of these leptoquarks to the Standard Model effective field theory. We present several scenarios, discussing in each case the preferred parameter space and the most relevant observables.